Reasons for the transformation of facilities management in the public sector - Buys, Fanie; Tonono, Erol (University of the Free State, 2007)
Facilities managers in the National Department of Public Works (NDPW) have to manage one of the biggest property portfolios in South Africa. This requires a systematic approach to ensure that taxpayers’ monies are not wasted. Research was conducted to determine whether the required policies and expertise are in place or whether there is a need for a transformation strategy in the public sector relating to facilities management. Primary data was collected by means of questionnaires to regional, property and facilities managers in the NDPW. Secondary data was obtained from the literature reviewed in relevant publications. The main findings were that more than half of facilities managers are inexperienced, information management systems are not used extensively and that there is a need for the appointment of properly trained facilities managers in the NDPW.

Fasiliteitsbestuurders in die Nasionale Departement van Openbare Werke (NDOW) is verantwoordelik vir die bestuur van een van die grootste eiendomsportfolios in Suid-Afrika. Hiervoor is ’n sistematiese benadering nodig om te verseker dat belastingbetalers se geld nie vermors word nie. Navorsing is gedoen om te bepaal of die nodige beleidsrigtinge en kundigheid reeds bestaan en of daar ’n behoefte is dat daar transformasie moet plaasvind rakende fasiliteitsbestuur in die NDOW. Primêre data vir die navorsing was verkry met behulp van vraelyste aan streeks-, eiendoms- en fasiliteitsbestuurders in die NDOW. Sekondêre data is verkry uit relevante bestaande literatuur. Die hoofresultate dui aan dat die meerderheid fasiliteitsbestuurders nie genoegsame kennis het nie, inligtingstelsels nie genoegsaam gebruik word nie en dat bevoegde fasiliteitsbestuurders dringend aangestel moet word.
Keywords: Facilities management; Transformation strategy; Public sector